2018
DOI: 10.1002/ccd.27711
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of routine preprocedural radial artery angiography in STEMI patients

Abstract: Routine preprocedural radial artery angiography in STEMI patients is associated with lower rate of access site bleeding complications and reduced overall procedural time and TRA crossover rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
(33 reference statements)
1
17
0
Order By: Relevance
“…Our hospital is a high volume transradial center (80% of all PCI interventions in the country) and the main referral center for primary PCI and complex procedures. Transradial approach has been the default approach in our center since 2008 21 , which is in accordance with the ESC guidelines for treatment of PCI patients [22][23][24] , and most probably has contributed to the low MACCE and mortality in our results [7][8][9] .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our hospital is a high volume transradial center (80% of all PCI interventions in the country) and the main referral center for primary PCI and complex procedures. Transradial approach has been the default approach in our center since 2008 21 , which is in accordance with the ESC guidelines for treatment of PCI patients [22][23][24] , and most probably has contributed to the low MACCE and mortality in our results [7][8][9] .…”
Section: Discussionsupporting
confidence: 71%
“…Pre-procedural retrograde radial arteriography was performed in all patients to define the radial artery anatomy from mid forearm to ulnobrachial anastomosis and to delineate ulnar artery anatomy as well, thus generating the access roadmap [6][7][8][9][10] .…”
Section: Methodsmentioning
confidence: 99%
“…Thus, for the routine use of radial artery angiograms and roadmaps, we advocate identifying radial artery tortuosity prior to wire passage. A recent study found that routine preprocedural radial artery angiography is associated with a lower rate of access site bleeding complications, reduced overall procedural time, and TRA crossover rate 30…”
Section: Radial Artery Anomalies and Tortuositymentioning
confidence: 99%
“…In the present study, trans-radial access and the use of mechanical support were significantly associated with MACE. Previous studies showed that trans-radial primary PCI was associated with less bleeding and long-term clinical outcomes [32][33][34]. However, we should mention the presence of selection bias regarding the access site.…”
Section: Plos Onementioning
confidence: 88%